Conference Scene: Scientists discuss the future of nanomedicine. (November 2013) - Geilich, Benjamin M; Webster, Thomas J
The First International Translational Nanomedicine Conference was recently held at Northeastern University (MA, USA) from 26 to 28 July 2013, in the heart of historic Boston (MA, USA). Sponsored by the International Journal of Nanomedicine and Northeastern University's College of Engineering, the conference focused on strategies for turning the advances in nanomedicine research into actual products, as well as addressing other issues pertinent to the future of the field. Plenary talks were given by distinguished Northeastern University faculty members for 1 h, and 30-min technical talks were given by experts from all over the world. Interspersed through the lectures, over 100 students and researchers presented posters detailing their latest findings.